Of the few Black coaches in Brazilian professional basketball leagues: approaches to racism - Marcelino, Julia Oliveira; Palma, Bartira Pereira; Galatti, Larissa Rafaela (Frontiers in Psychology, 2025)
IntroductionWithin Brazilian sports, Black individuals are significantly underrepresented in leadership roles, a disparity especially evident in elite sporting spheres, which remain highly exclusive. This study aimed to investigate the perceptions of Black elite basketball coaches regarding the impact of racism on their professional trajectories within Brazilian professional basketball leagues.MethodsSemi-structured interviews were conducted with four Black professional basketball coaches (two men and two women) working or who had worked in Brazil’s primary leagues, the NBB (Novo Basquete Brasil—New Basketball Brazil) and the LBF (Liga de Basquete Feminino—Women’s Basketball League). Data were analyzed using reflexive thematic analysis.ResultsFive broad themes and seven subthemes emerged from the narratives: (1) Support Network, encompassing the individuals, events, and environments that shaped their careers; (2) Combating Racism, detailing strategies developed to cope with racism, with two subthemes: (a) Blaming the Victim, and (b) Dealing with Racism; (3) Barriers, describing obstacles that complicated their professional journeys, with three subthemes: (a) Questioning Professional Competence, (b) Disadvantages, and (c) Perception of Structural Racism; (4) Black Individuals in Leadership Roles, emphasizing the importance of visibility and representation, with two subthemes: (a) Identity, capturing their self-recognition as Black individuals, and (b) Importance of Black Individuals in Leadership Roles; and (5) Accumulation of Prejudices, highlighting the compounded effects of racial and other intersecting biases.DiscussionThe findings emphasize the urgent need for policies promoting a more inclusive and equitable environment for Black basketball coaches in Brazil. Tailored interventions addressing the unique challenges encountered by Black male and female coaches could mitigate the impacts of structural racism. Implementing such strategies could foster a more just landscape within Brazilian basketball, providing Black coaches with enhanced opportunities to succeed and contribute in leadership roles.